Global implications of modern enterprise information systems technologies and applications - Gunasekaran, Angappa (Advances in enterprise information systems (AEIS), 2009)
"This book presents useful strategies, techniques, and tools for the successful design, development, and implementation of enterprise information systems" - Provided by publisher